Strategi Pemasaran Digital Melalui Analisis SWOT Dalam Meningkatkan Penjualan Ditengah Pandemi Covid 19 (Studi Kasus Kripik Tempe Sari Rasa Sanan Di Malang) - Ayu Rizki Wulandari; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study qualitatively analyzes the Digital Marketing Strategy through Swot Analysis in Increasing Sales Volume Amid the Covid 19 Pandemic (Case Study of Keripik Tempe Sari Rasa Sanan in Malang).The data collection method used is documentation. Based on the results of research and discussion of digital marketing strategies on sales volume to take advantage of opportunities and fight existing threats, Keripik Tempe Sari Rasa Sanan utilizes Instagram and Facebook social media well through ig or facebook ads. By doing digital marketing, it really helps to increase revenue which is also automatically accompanied by an increase in sales volume as well. This is proof that digital marketing has a big influence in increasing sales volume in the UMKM Sanan Tempe Chips business. Keywords: Digital Marketing, Sales Volume, Instagram, Facebook Ads